Patent Landscape and Applications of Organic Menthol Crystals: An In-Depth Analysis of Emerging Trends and Industrial Applications - Reda El Boukhari; Ahmed Fatimi (Chemistry Proceedings)
Menthol, a cyclic monoterpene alcohol commonly derived from mint essential oils, is widely utilized across the pharmaceutical, cosmetic, and personal care industries due to its cooling, analgesic, and aromatic properties. This study presents a comprehensive patent landscape analysis of organic menthol crystals and their derivatives, with a focus on identifying current trends and emerging applications. Patent data were retrieved from The Lens and Google Patents, and 23,515 relevant patents were analyzed using international patent classification codes. The results revealed significant applications in pharmaceuticals, personal care, and drug delivery systems, with notable innovations in controlled-release formulations, cancer treatments, and pain relief products. Emerging trends include the combination of menthol with other natural compounds, advances in microencapsulation for controlled drug delivery, and its use as flavor enhancement in the tobacco industry. The United States leads in menthol-related patents, followed by China and the European Union. This analysis provides valuable insights into the future of menthol applications, suggesting that its role in therapeutic and cosmetic industries will continue to grow, driven by technological advancements and regulatory factors.